TEACHERS’ PROFESSIONAL DEVELOPMENT AND REINFORCEMENT AT INTEGRATED ISLAMIC SCHOOLS IN INDONESIA - Siregar, Zulfikar Ali Buto; Arsyad, Junaidi; Hanum, Azizah; Ritonga, Maisaroh; Mohd Jamil, Mohd Ridhuan (Universitas Islam Negeri Ar-Raniry, 2025)
The development of Integrated Islamic Primary Schools is in response to the society’s increasing demand for quality graduates. Thus, the emphasis on the effectiveness of learning in Integrated Islamic Primary Schools (IIPS) necessitates institutional innovation and teacher professionalism. This research investigates the professionalism in IIPS and determines the factors that contribute to teachers' professional practices. The study is qualitative with a phenomenological approach. This study employed the “Tarbiyah learning framework” developed by Abdurahman Al-Nahlawi, and the data were collected through in-depth interviews and observations to investigate the dimensions of teacher professionalism, teaching methodologies, and factors affecting teacher professionalism. The findings reveal that there is a mismatch between professional development initiatives and the actual conditions faced by students. Teaching-learning process that is responsive to students needs and characteristics, collaborative learning programs and supervision sctivities are all viable strategies. Teacher professionalism can be identified by demonstrating strong commitment and work discipline. The IIPS also provides structured training programs and collaborative partnerships with the education office to improve relevant teaching competencies and methodologies. Further, the social implications of this research include the availability of high-quality educational options for the community at the primary school level. Furthermore, the varied management system of IIPS serves as a social control to ensure the quality of primary education continues to develop.